THU0093 Clinical, radiographic, and immunogenic effects after 1 year of tocilizumab (TCZ)-based treatment strategy with and without methotrexate (MTX) in RA: The act-ray study. (23rd January 2014) - Dougados, M.; Kissel, K.; Conaghan, P.G.; Martin-Mola, E.; Schett, G.; Amital, H.; Xavier, R.M.; Troum, O.; Bernasconi, C.; Huizinga, T.W.J.
Abstract : Background: 24-week data from ACT-RAY comparing an add-on strategy (TCZ+MTX) with a switch strategy (TCZ+placebo [PBO]) in MTX-IR patients have been previously reported, demonstrating relevant clinical and radiographic benefit without a statistically significant difference between the 2 groups. Longer-term data are needed to assess the 2 strategies over time and the effect of the protocol-specified treat-to-target strategy after Week 24. Objectives: To assess the 52 week efficacy and safety of a TCZ-based adaptive treatment strategy with and without MTX in adult patients with moderate to severe RA and an inadequate response to MTX. Methods: ACT-RAY is a phase 3b clinical trial. Patients on stable doses of MTX were randomized to either add TCZ 8 mg/kg IV every 4 weeks to their existing MTX or switch to TCZ 8 mg/kg IV every 4 weeks with oral PBO. Open-label DMARDs other than MTX were added at Week 24 or later, usually if DAS28 was >3.2, maintaining blinding of MTX/PBO. Groups are labeled "TCZ+MTX" and "TCZ+PBO" despite treatment modifications in both groups. Results: 556 patients were randomized, with 85% completing 52 weeks of treatment. Baseline data were similar between the 2 groups except for Genant-modified Sharp Score, which was higher in the TCZ+PBO group. Between weeks 24 and 52, the proportion of patients receiving DMARD intensification was comparable in the TCZ+MTX and TCZ+PBO arms (29% vs 33%). Efficacy results are shown in the table. Efficacy was maintained or improved from Week 24 to 52. Most patients had no radiographic progression from baseline to 52 weeks >1.5 (smallest detectable change [SDC]). Rates of SAEs and serious infections per 100 PY were 14.2 and 4.9 for TCZ+MTX and 17.7 and 6.3 for TCZ+PBO, respectively. In patients with normal baseline values, ALT elevations >60U/L were observed in 36% of TCZ+MTX and 17% of TCZ+PBO patients. Antidrug antibodies (ADAs) were detected in 4.7% of patients (10/215) in the TCZ+MTX group and 5.4% (11/204) in the TCZ+PBO group up to week 52. Neutralizing ADAs were detected in 3.7% of patients (8/215) in the TCZ+MTX group and 4.4% (8/204) in the TCZ+PBO. Conclusions: Clinical improvements at Week 24 in both groups were maintained or further improved up to Week 52, with the proportion of patients receiving DMARD intensification comparable between TCZ+MTX and TCZ+PBO. The vast majority of patients showed no radiographic progression of structural damage. The proportion of patients with ADAs was similar in both groups. Generally there were no differences in safety between the 2 groups. These data support the possibility of using TCZ monotherapy in patients with contraindications or intolerance to MTX. Disclosure of Interest: M. Dougados Grant/Research support from: Roche, Consultant for: Roche, K. Kissel Employee of: F. Hoffmann-La Roche Ltd., P. Conaghan Grant/Research support from: Centocor Inc., Roche, Speakers Bureau: Astra Zeneca, Bioberica, Bristol-Meyers Squibb, Centocor Inc., Merck, Novartis, Pfizer, Roche, E. Martin-Mola Consultant for: Abbott Immunology, Roche MSD, Pfizer, UCB, G. Schett Consultant for: Roche, H. Amital: None Declared, R. Xavier Consultant for: Pfizer, Speakers Bureau: Pfizer, Roche, Merck, O. Troum Grant/Research support from: Genentech, Consultant for: Genentech, C. Bernasconi Employee of: F. Hoffmann-La Roche Ltd., T. J. Huizinga Consultant for: Abbott Immunology, Axis Shield Diagnostics, Biotest AG, Bristol-Meyers Squibb, Crescendo Bioscience, Roche, Novartis, Schering-Plough, UCB, Wyeth-Pfizer